Child labour and sexual exploitation in Bangladesh: Analysis of government failure to protect children's rights within the constitutional framework - Lalu Ary Kurniawan Hardi; Casey Alexa Kruger; Richard Anderson; Ryanta Septario Yudhananta; Irfan Rafi Maulana; Celine Chelsea Amelia Afaratu; Nicky Emmanuel Simanjuntak; Chantya Rania Syaikha Jatmiko; Taufik Hidayat; Fahanza Dalih Al Faraz (Universitas Airlangga, 2025)
In the context of the constitution and in its execution, the state is now required to satisfy the rights of its citizens, particularly the rights of children. Nonetheless, many nations around the world continue to fail to fully enforce these rights, which would lead to social discontent. Bangladesh is one of these nations, with a high prevalence of abuses of children's rights. With an emphasis on child labor, sexual exploitation, and the government's policy reaction, this study uses a qualitative research approach and a thorough literature analysis to investigate child rights abuses in Bangladesh. Peer-reviewed scholarly journals, official government publications, and reports from international organizations were among the many secondary sources from which the data were collected. Despite the existing legal and constitutional framework for protecting children's rights, child labour and sexual exploitation still happens regularly. It is found that the root causes of these phenomenon are poverty and religio-cultural values in Bangladesh’s society. Thus addressing these problems could help to further make existing laws to protect children’s rights even more systemic.